INNATE IMMUNITY IN OSTEOARTHRITIS IN COMORBIDITY WITH NON-ALCOHOLIC STEATOHEPATITIS IN PATIENTS WITH HELICOBACTER PYLORI INFECTION - Loskutov, A.L.; Loskutova, I.V. (World of Medicine and Biology, 2021)
The pathogenesis of comorbid pathology of joints and liver in patients infected with Helicobacter pylori is considered in the study. We examined 57 patients with osteoarthritis in comorbidity with non-alcoholic steatohepatitis, of whom 23 showed specific antibodies to Helicobacter pylori without clinical and instrumental manifestations of gastric and duodenal mucosa. The study revealed a decrease in phagocytic activity of monocytes, the number of populations of NK lymphocytes, which can be characterized as a lack of nonspecific reactivity in the examined patients. There was a significant decrease in phagocytic activity of monocytes with activation of nonspecific reactivity of the body (increase in the number of NK lymphocytes), growth of serum proinflammatory (IL-8, IL-12) cytokines, against the background of Helicobacter pylori infection in osteoarthritis in comorbidity with non-alcoholic steatohepatitis, indicating the presence of chronic systemic inflammation. The study of the level of cytokines and innate immune factors in the comorbid course of osteoarthritis and non-alcoholic steatohepatitis on the background of Helicobacter pylori infection can be used to predict the further progression of the inflammatory reaction in the liver, the intensity of immunopathological reactions in the joints and the development of pathogenetic therapy methods of the specified category of patients.
Keywords: osteoarthritis; non-alcoholic steatohepatitis; Helicobacter pylori; innate immunity; phagocytic activity of monocytes; cytokines